Trends in the manifestation of honour and dignity among students of different majors in the time of social transformations - Н. Venherova,; Н. Lutsenko,; I. Zuiev, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The aim of this study is to examine hounor and dignity manifestations of university students of different learning areas in the time of social transformations. It was used V. V. Rybalka's ‘Inventory for approximate finding of hounor and dignity personality manifestations'. It measures indi- cators of hounor and dignity general level, separate indicators of hounor and dignity feeling intensity and subscale indicators of hounor and dignity manifestations in the motivational, cognitive, aim-forming, operation-resultant and emotional-feeling personality spheres. The study sample in- cluded 291 students. In details it were tested 48 students-psychologists of 1st year studying in December 2013, 33 students-psychologists of 5th year studying in February 2014, 28 students-psychologists of 5th year studying in September 2014, 59 students-biologists of 1st year studying in May 2014, 28 students-biologists of 5th year studying in September 2014, 31 students-chemist of 1st year studying in April 2014, 36 students-chemist of 5th year studying in May 2014 and 28 students-chemist of 5th year studying in September 2014. In this time in Ukraine was taking place such political events as ‘Maydan', Crimea annexation and war in the Donbas. As a result it was found that the highest level of hounor and dignity is peculiar to the students-biologists that can be explained by their need for labor market. During the considered period the hounor and dignity level of students- psychologists and chemicals at first was decreased (in winter and spring 2014), and then increased (in September 2014). We think that student's- chemicals increasing of hounor and dignity feelings were connected with political situation improvement, and student's-psychologists increasing of hounor and dignity feelings is related to their active role in volunteer movement.
Keywords: honour, dignity, students, social transformations.